ENTREPRENEURIAL MOTIVATION AND ITS IMPACT ON MOMPRENEUR BUSINESS PERFORMANCE (STUDY ON SONGKET AND BATIK WOMEN ENTREPRENEURS IN JAMBI CITY) - Erwita Dewi (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Women entrepreneurs have become a rapidly growing phenomenon in the last decade. In the province of Jambi, the development of the MSME sector has also continued to increase, as has the case in the city of Jambi. Female MSMEs are dominated by housewives and those who already have children are also known as